Employee Engagement Factors in A Higher Education Institution - Ahmad Azmy (Binus Business Review, 2019)
This reseach analyzed factors that correlated with employee engagement in a higher education institution. The object of this research was the lecturers and employees with the total of 100 people. There were measured on how to produce academic quality accompanied by excellent service to students. Dimensions used were compensation, leadership and organizational planning, culture and corporate communication, job environment, supervisory relationships, employee satisfaction and training, development, and resources. The process of collecting data was through the questionnaires. The research method used Confirmatory Factor Analysis (CFA). In the results, all dimensions used have a significant influence on employee engagement because of p-values <0,05 and t-tables > t-statistics. The supervisor relationship dimension has the highest correlation of 66,5%, and employee satisfaction has the lowest correlation of 13,8%. Higher education institutions must increase employee engagement to maintain productivity and performance. Employee engagement is one of the keys to the success of educational institutions to produce exceptional academic quality and services for the entire academic community.